Improving Students’ Self-Efficacy in Studying Salt Hydrolysis using the SCCrT Model - Rusmansyah, Rusmansyah; Huda, Nurul; Mahdian, Mahdian; Hamid, Abdul; Aufa, Mohamad Nor; Safitri, Linda (FKIP Universitas Lampung, 2023)
Improving Students’ Self-Efficacy in Studying Salt Hydrolysis Using the SCCrT Model. Objectives: This study aims to determine the differences in the Self-Efficacy of students who learn to use the SCCrT (Scientific Critical Creative Thinking) model with the DI (Direct Instruction) model. Methods: This research is an experimental study of quasi-experimental design with a sample of 69 people consisting of 2 classes with data collection techniques using a questionnaire consisting of 15 statements using four aspects of self-efficacy. Data analysis was descriptive quantitative, and quantitative inferential with SPSS version 25. Findings: The application of the SCCrT model affects students' self-efficacy acquisition, which is characterized by differences in the self-efficacy results with classes that apply the DI model with an average significance value of 0.00. Conclusion: There are differences in students’ self-efficacy between classes that study with the SCCrT model and courses that use the DI model. The SCCrT model performed better than the DI model in the average category, and the DI model performed well in the salt hydrolysis material category. Keywords: self-efficacy, salt hydrolysis, SCCrT model.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202322